2010
DOI: 10.4161/cc.9.12.12050
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional crosstalk between TGFβ and stem cell pathways in tumor cell invasion: Role of EMT promoting Smad complexes

Abstract: Tumor cells undergoing the epithelial-mesenchymal transition (EMT) acquire the capacity to migrate, invade the stroma and metastasize. EMT cells also acquire stem cell characteristics suggesting crosstalk between EMT and stem cell pathways and contribution of the EMT process to the generation of cancer stem cells. Indeed, transforming growth factor-beta (TGF-β), a major inducer of EMT, cooperates with stem cell pathways like Wnt, Ras, Hedgehog and Notch to induce EMT. A molecular basis for this cooperative sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
241
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(251 citation statements)
references
References 177 publications
(213 reference statements)
7
241
1
2
Order By: Relevance
“…38,39 Comparison to human samples that contained a progression spectrum of grade and stage confirmed that phosphorylation of SMAD2 was increased in advanced lesions. A similar result was seen in our cell lines, in which the high-grade bladder cancer cells UMUC3, T24, and J82 showed TGF-b pathway activation relative to the more epithelioid RT4 bladder cancer cells, which lacked critical elements, such as the TGF-bR1 isoform and SMAD4, and which expressed E-cadherin.…”
Section: Tgf-b/mtorc2 In Bladder Cancer Invasionmentioning
confidence: 89%
“…38,39 Comparison to human samples that contained a progression spectrum of grade and stage confirmed that phosphorylation of SMAD2 was increased in advanced lesions. A similar result was seen in our cell lines, in which the high-grade bladder cancer cells UMUC3, T24, and J82 showed TGF-b pathway activation relative to the more epithelioid RT4 bladder cancer cells, which lacked critical elements, such as the TGF-bR1 isoform and SMAD4, and which expressed E-cadherin.…”
Section: Tgf-b/mtorc2 In Bladder Cancer Invasionmentioning
confidence: 89%
“…This is consistent with the reported crosstalk between Zeb and Smad proteins on Smadresponsive promoters. 41 Reduced snai2/Slug was also observed upon Zeb1/2 knockdown (Figures 6a and c), likely due to decreased TGFβ pathway activity. These data indicate that decreasing Zeb1 and/or Zeb2 in EpFra1 cells restored a significant part of the epithelial programme.…”
Section: Epfra1-sz2mentioning
confidence: 94%
“…43,44 TGF-b, which induces the TGFBI protein, has a reported role in the regulation of TCF4 and ZEB1 through signaling pathways in EMT. 26 Mutations in TGFBI cause some human corneal dystrophies, but have not been reported to cause FED. 2 Our study has revealed the first possible association of TGFBI with FED and upregulation of TGFBI in the corneal epithelium in FED.…”
Section: Association Of Tcf4 and Clu Polymorphisms With Fedmentioning
confidence: 99%
“…TGFBI is induced by the TGF-b (transforming growth factor-b) gene. 26 Interestingly, TGF-b reportedly regulates both TCF4 and ZEB1, which have been implicated in FED. 27 This study investigated association of the reported polymorphisms in the TCF4 and PTPRG genes in Australian FED cases.…”
Section: Introductionmentioning
confidence: 99%